Gneiss Domes in Orogeny 2004
DOI: 10.1130/0-8137-2380-9.129
|View full text |Cite
|
Sign up to set email alerts
|

Exhumation of orogenic crust: Diapiric ascent versus low-angle normal faulting

Abstract: Many high-grade metamorphic terrains record isothermal decompression, implying rapid exhumation or heat input during decompression. These terrains commonly contain gneiss domes that are spatially and temporally associated with low-angle normal faults such as those bounding metamorphic core complexes. To understand the thermomechanical relationship of gneiss domes and core complexes, we use twodimensional numerical modeling to evaluate exhumation and cooling rates resulting from diapiric ascent of partially-mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 52 publications
1
16
0
Order By: Relevance
“…Overprinting textures of cordierite possibly record decompression of footwall rocks due to translation upon the detachment structure; and the late-tectonic melt-filled, normal-sense shear bands that cut all older structures may be an indication of a small volume of late leucogranite formed by decompression-induced melting (Siddoway et al, 2004b;Korhonen et al, 2007b). The very high rates of cooling recorded by 40 Ar/ 39 Ar mineral cooling data are comparable to rates of advective heat loss that arise from pluton emplacement in cold country rock (Fayon et al, 2004). These observations are possible indications of a component of upward, gravity-driven flow (diapirism) during emplacement of the dome (e.g., Teyssier and Whitney, 2002).…”
Section: Overview Of the West Antarctic Rift Systemsupporting
confidence: 53%
“…Overprinting textures of cordierite possibly record decompression of footwall rocks due to translation upon the detachment structure; and the late-tectonic melt-filled, normal-sense shear bands that cut all older structures may be an indication of a small volume of late leucogranite formed by decompression-induced melting (Siddoway et al, 2004b;Korhonen et al, 2007b). The very high rates of cooling recorded by 40 Ar/ 39 Ar mineral cooling data are comparable to rates of advective heat loss that arise from pluton emplacement in cold country rock (Fayon et al, 2004). These observations are possible indications of a component of upward, gravity-driven flow (diapirism) during emplacement of the dome (e.g., Teyssier and Whitney, 2002).…”
Section: Overview Of the West Antarctic Rift Systemsupporting
confidence: 53%
“…Although the tectonic regimes for such detachment systems are quite distinct from those forming the STDS (crustal extension vs. crustal shortening), the fault geometry and relative contrasts in T and peak metamorphic conditions are comparable. Numerical models of such detachment system geometry suggest that it is not possible to isothermally decompress footwall rocks by normal fault displacement in the absence of an additional heat source [ Fayon et al ., ]. Fayon et al .…”
Section: Discussionmentioning
confidence: 99%
“…Fayon et al . [] found that relatively steep fault angles (30°) are required to achieve significant decompression in the footwall of a detachment by normal slip on the structure. This results in a juxtaposition of hot footwall rocks against colder hanging wall rocks and thus cooling of the footwall during decompression.…”
Section: Discussionmentioning
confidence: 99%
“…Buck, 1991;Wernike, 1992). The concept evolved mainly toward understanding crustal flow involving extension and thinning of thick and hot crust, leading to the formation of a large diversity of metamorphic core complexes cored by migmatite domes that are bounded by vertical or usually low angle faults (Fayon et al, 2004;Dunkl and Frisch, 2002). Models of crustal partial melting related with crustal flow have been also developed (e.g.…”
Section: Discussion 61 Extension and Magma Generationmentioning
confidence: 99%